The Relationship Between Self-Concept with Depression Degree in Hypertensive Patient - Baharuddin Baharuddin; Israwati Israwati (Humanistic Network for Science and Technology (HNST), 2017)
In hypertensive patients, a negative self-concept (body-image, self- ideal, self-esteem, self-role and self-identity) will trigger a depression. The purpose of this study was to analyze the relationship between self-concept with the degree of depression in hypertensive patients at the Masalle Community Health Center, Masalle Sub District, Enrekang District. The subjects of this cross sectional study were 71 hypertensive patients selected by purposive sampling technique. Data were collected through questionnaire, then analyzed descriptively in the form of frequency and percentage, then continued with Chi square test, and ended with multiple linear regression test. The results of data analysis show that body-image and self-esteem is associated with the degree of depression in hypertensive patients. Key words: Depression, Hypertension, Self-concept